Safety and Efficacy of Therapeutic Cancer Vaccines Alone or in Combination With Immune Checkpoint Inhibitors in Cancer Treatment - Zhao, Jing; Chen, Ye; Ding, Zhen-Yu; Liu, Ji-Yan (Frontiers in Pharmacology, 2019)
Therapeutic cancer vaccines have proven to seldom induce dramatic clinical response when used alone, and therefore, they are being studied in combination with additional treatment modalities to achieve optimal treatment activities. Growing preclinical data shows that combining vaccines and immune checkpoint inhibitors (ICIs) can prime intensified immunogenicity and modulate immunosuppressive tumor microenvironment. Herein, we focus on the safety and efficacy of approved and promising cancer vaccines alone or combined with ICIs in the treatment of several malignancies. Generally, the majority of clinical trials support the concept of synergy that combination therapy of vaccines and ICIs holds maximized potential to improve clinical outcomes; Importantly, the combination has acceptable safety and minimal additional toxicity compared with single agent vaccines or ICIs. Additionally, the potential strategies of combining personalized tumor vaccines with ICIs will become priority option and future direction of vaccine development and application, and the urgent need to develop effective biomarkers to screen appropriate patient populations and predict response to combination therapy.